Gender, Worker Representation and the Profitability of Firms in Germany - Uwe Jirjahn (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2011)
Recent research has shown that the unexplained gender wage gap is smaller in establishments where a works council is present. The finding raises the question of whether establishment-level codetermination reduces gender wage discrimination or whether it reduces a wage differential that reflects productivity differences between men and women. This study addresses the question by examining the association between the share of female employees and profitability. Using data from manufacturing establishments, the empirical analysis suggests that there is a positive association between the share of women and profitability in establishments without a works council while there is no association in establishments with a works council. These results support the hypothesis that establishment-level codetermination reduces gender-specific wage discrimination.
Keywords: J33; J51; J53; J71; 330; Women; Discrimination; Profitability; Works Councils; Piece Rates